PERAN PERCEIVED VALUE DAN FREQUENCY CONSUMPTION TERHADAP REPURCHASE INTENTION KONSUMSI BUAH DI MASA PANDEMI COVID-19 - Audrina, Sheila Okthalia; Immanuel, Dewi Mustikasari (Ma Chung Press, 2023)
This study aims to determine the effect of healthy consumption, perceived price fairness, and perceived quality on repurchase intention to consume fruits during the COVID-19 pandemic with frequency consumption as a moderator and perceived value as a mediator. Questionnaire data is processed using PLS. The population in this study were people who had bought fruit in Surabaya and Sidoarjo. The sampling technique used was purposive sampling with a total sample of 386 respondents. The results of this study indicate that healthy consumption, perceived price fairness, and perceived quality have a positive effect on repurchase intention, and perceived value provides a full mediating effect, while frequency consumption as a moderator is found to weaken the effect of healthy consumption on repurchase intention. Keywords: Healthy consumption, frequency consumption, perceived price fairness, perceived quality, perceived value, and repurchase intention.